Exploring Hermeneutic Through Lyrics of the Song “Akhir Tak Bahagia”: A Case on Critical Discourse Analysis - Ratna saputri saragih; Klara kristina Malaub; Nikerian W, Manik; Widya Ambarita; Nopaulina Sinagae; Herman Herman (Universitas Pahlawan Tuanku Tambusai, 2023)
The goal of this research was focused more on Wilhelm Dilthey's hermeneutic theory to examine the lyrics of the song